DoD and Commercial Advanced Waveform Developments and Programs with Multiple Nunn-McCurdy Breaches, Volume 5 - Arena, Mark V. (RAND Corporation, 2014)
The report presents the results of two studies: The first compares the capabilities and development approaches used in the Joint Tactical Radio System wideband networking waveform and the commercial long-term evolution waveform, and the second analyzes military acquisition programs that have exceeded certain cost thresholds more than once.